Optimasi Produksi Tanaman Kedelai Edamame (Glicine max. (L) Merrill) Dengan Pengaturan Jarak Tanam Dan Pemberian Kompos - Yuriansyah; Lisa Erfa; Evi Yunita S Sari (Jurnal Penelitian Pertanian Terapan, 2023)
Soybean plants (Glycine max (L) Merrill) are annual plants, have white or purple flower colors and have various shapes and sizes for leaf and seed characters. Soybean production in Lampung province in 2015 was 9.82 thousand tons of dry beans, decreased by 3.96 thousand tons (28.76%) compared to 2014. Crop productivity is strongly influenced by the environment and the variety of plants planted, and the spacing is also closely related to the plant population. Spacing arrangement is very influential on plant growth and yield. One of the efforts that can be done to improve soil fertility is by giving compost. Compost is the final substance of a fermentation process of piles of garbage / plant litter and sometimes also includes animal carcasses. This study used a randomized block design with 3 replications, the treatment was given 2 factors, spacing and compost application. The purpose of this study was to increase the yield of edamame soybean optimally with the treatment of spacing and giving organic compost. The results showed that based on least significant different show that the best interaction between spacing planting and compost application on all variable is J2K2 (15cm x 40cm + 12 ton/ha). While the lowest treatment on the J0K0 (15cm x 20cm + 0 ton/ha).